Immunogenetics - Bontrop, Ronald E.; Kasahara, Masanori; Flajnik, Martin; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Immunogenetics publishes original papers, brief communications, and reviews on research in the following areas: genetics and evolution of the immune system; genetic control of immune response and disease susceptibility; bioinformatics of the immune system; structure of immunologically important molecules; and immunogenetics of reproductive biology, tissue differentiation, and development.
Keywords: Human genetics; Medical genetics; Immunology; Allergy; Cell biology; Immunology; Human Genetics; Gene Function; Cell Biology; Allergology